Gambaran Gejala Pasien Covid-19 dengan Komorbiditas Tuberkulosis di Rumah Sakit Al-Ihsan Kabupaten Bandung 2020-2022 - Reynindita Alya Harsyanti; Mia Kusmiati; Dony Septriana Rosady (Bandung Conference Series: Medical Science, 2024)
Abstract. Coronavirus Disease is an acute respiratory infectious disease. COVID-19 cases are rapidly increasing and spreading throughout Indonesia and have an impact on the number of deaths of the population.. The purpose of this study was to understand the differences in COVID-19 symptoms with Tuberculosis and non-Tuberculosis comorbidities at RSUD Al Ihsan Bandung. The purpose of this study was to understand the differences in COVID-19 symptoms with Tuberculosis and non-Tuberculosis comorbidities at RSUD Al Ihsan Bandung. The research method used in this study was descriptive using the Chi –Square statistical test to see the difference between COVID-19 and Tuberculosis and non-Tuberculosis comorbidities. The subjects of this study were patients confirmed with COVID-19 with Tuberculosis and Non-Tuberculosis comorbidities at RSUD Al Ihsan Bandung 2020-2022. Most tuberculosis patients were male 208 people (57.6%) and non-tuberculosis patients dominated by women 183 people (50.7%), The results showed that patients confirmed positive for COVID-19 with the most comorbid tuberculosis with mild symptoms especially shortness of breath were 202 people (55.9%) while 193 people (53.5%) non-tuberculosis comorbid patienst.It was concluded that there were significant differences between COVID-19 with pulmonary tuberculosis comorbidities and COVID-19 patients with non-tuberculosis comorbidities. Abstrak. Coronavirus Disease adalah penyakit infeksi saluran pernapasan akut. Kasus COVID-19 dengan cepat meningkat dan menyebar ke seluruh Indonesia serta berdampak pada jumlah kematian populasi. Tujuan dilakukannya penelitian ini adalah untuk memahami perbedaan gejala COVID-19 dengan komorbiditas Tuberkulosis dan non Tuberkulosis di RSUD Al Ihsan Bandung. Metode penelitian yang digunakan dalam penelitian ini adalah deskriptif dengan menggunakan uji statistik Chi –Square untuk melihat perbedaan antara COVID-19 dengan komorbiditas Tuberkulosis dan non Tuberkulosis. Subjek penelitian ini adalah pasien yang terkonfirmasi COVID-19 dengan komorbiditas Tuberkulosis dan Non Tuberkulosis di RSUD Al Ihsan Bandung sebanyak 722 orang. Sebagian besar pasien Tuberkulosis berjenis kelamin laki-laki 208 orang (57,6%) dan pasien non Tuberkulosis didominasi perempuan 183 orang (50,7%), Hasil penelitian menunjukkan pasien terkonfirmasi positif COVID-19 dengan komorbid Tuberkulosis paling banyak yaitu pada gejala ringan terutama pada sesak nafas sebanyak 202 orang (55.9%) sedangkan pada pasien komorbid Non Tuberkulosis 193 orang (53.5%) Disimpulkan terdapat perbedaan yang signifikan antara COVID-19 dengan komorbiditas Tuberkulosis paru dan pasien COVID-19 dengan komorbiditas non Tuberkulosis.